Phenology of Flowering and Pod Maturity on Some Cocoa Clones (Theobroma cacao L) - Indah Anita Sari; Agung Wahyu Susilo (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2015)
Phenology  of  flowering  is  an  important  aspect  in  the  growth  cycle  of cocoa (Theobroma  cacao L.) because the  performance of  plant  especially  flowering is  linked with  anthesis time, time and  duration  of  stigma  receptivity, fruit formation, crossing,  and  seed  development  which  determine  the  plant  breeding  programs . Research was conducted at the Kaliwining experimental station of Indonesian Coffee and  Cocoa  Research Institute  (ICCRI).  The  cocoa  plant  was  originated  from  top grafting seedling  with the age  of eight  years.  Design  of  experiment  was  randomized complete  block  design  consisted  of  eight  clones  as  treatment  with  three  replications.  Each  plot  consisted  of  20  sample  flowers.  The  parameters  observed  were phenology  of  flowering  and  pod  maturity.  Phenology  of  flowering  observed  were age  of  flowering,  number  of  opened  flower  buds,  number  of  flower  buds  that dropped  before  being  opened,  number  of  flower  buds  that  dropped  after  being opened,  and  number  of  opening  flowers  that  developed  into  tiny  fruits.  Observation  on  pod  and  been  quality  was  done  on  pod  size,  pod  weight,  pod  length, pod  girth,  and  bean  number.  The  result  of  experiment  showed  that  difference  in phenologyof  flowering and age of pod maturity  existed within eight cocoa clones tested.  KKM  22  showed  the  shortest  flowering  age  and  pod  maturity,  and  lowest number  of  beans.  The  highest  success  of  pollination  was  observed  on  Sca  6  and KW 617. ICCRI 03, Sulawesi 03, ICCRI 07, KKM 22 and KW 617 showed relative low success of  pollination,  that  iswas between 10  to 17.6%.  Age  of  flower  opening did  not  significantly  influence  age  of  pod maturity,  on  the  other  hand  it  did  not negatively  influence  percentage  of  flower  opening  and  percentage  of  pollinated flowers. The characteristic of flowering age had high genetic coefficient of variation as  well  as  high  estimated  value  of  heritability.  Percentage  number  of  flower buds  that  dropped  before  open  showed  high  genotypic  and  phenotypic  coefficient  of  variation,  however  the  estimated  heritability  was  grouped  in  low  category. The  characteristic  of  pod maturity   age,  percentage  of  flower  opening  and  bean number  in  each  pod had  low  values  of  genotypic  and  phenotypic  coefficient  of variation,and  low  heritability.